ORGANIZATIONAL FORMS OF COMPUTER SCIENCE EDUCATION - Muydinjonov Ziyodjon Rafiqjon Ugli; Muydinjonov Davlatjon Rafiqjon Ugli; Madrakhimova Makhfuza Akhmedovna; Madrakhimov Shukhratjon Shukurovich (Galaxy International Interdisciplinary Research Journal, 2022)
Student activity is part of the interaction between the participants of the educational process. There are also forms that provide for the individual activity of students. Organizational forms of teaching occupy one of the central places in computer science didactics and teaching methodology. This article describes organizational forms of computer science education.